Effect Of Gel Polymer Organic Mineral Addition in Cement Compositions (Texas Journal of Multidisciplinary Studies, 2021)
The article examines the hardening of binder compositions with the addition of gel-polymer additives in different temperature and humidity conditions. High levels of crystallization of hydrated components of the final stage of hydration have been studied, while gelpolymers not only retain moisture well in the concrete microstructure, but also actively participate in the process of structure formation.